Front Cover: Learning From Vitamin B12‐Mediated Reactions: Cobalt(III)−Carbon‐Assisted Catalytic C−H Difluoroacylation of (Hetero)Arenes through Controlled‐Potential Electrolysis (ChemElectroChem 16/2019). Issue 16 (29th July 2019) - Hossain, Md. Jakir; Ono, Toshikazu; Yano, Yoshio; Hisaeda, Yoshio
Abstract : The Front Cover shows the electrochemical activation of a vitamin B12 catalyst as well as the obtained difluoroacylated products. More information can be found in the Article by Md. J. Hossain et al. onpage 4199 in Issue 16, 2019 (DOI:10.1002/celc.201900164 ).